What Does Antidepressant Drug level Monitoring Reveal About Outpatient Treatment and Patient Adherence? - Silhan, Petr; Urinovska, Romana; Kacirova, Ivana; Hyza, Martin; Grundmann, Milan; Ceskova, Eva (Pharmacopsychiatry, 2019)
Introduction The evaluation of plasma levels of antidepressants may improve the treatment outcome. The aim was to verify adherence and adequacy of administered doses of antidepressants among patients hospitalized for inadequate outpatient therapeutic response.Methods Selective serotonin reuptake inhibitors or venlafaxine plasma levels were assessed on the first day of hospitalization and after 3 days of controlled administration. The patients were considered adherent if the plasma level on admission was within the interval of the minimum and maximum plasma level on the fourth day, expanded by 30%. The adequacy of antidepressant doses used during the outpatient treatment was assessed by comparing the plasma level on the fourth day with the therapeutic reference range.Results Out of 83 patients, 52 (62.7%) were adherent. The plasma levels of antidepressants on the fourth day were found to be within the therapeutic reference range in 35 (43.2%) patients. The same number manifested levels below the therapeutic reference range. In 11 (13.6%) patients, the levels were higher than recommended. No significant difference in rate of adherence was found among individual antidepressants.Conclusion The results show that antidepressant nonresponders are frequently under-dosed or nonadherent.
Keywords: adherence; depression; antidepressants; plasma levels; therapeutic drug monitoring